ANALISIS SIKAP KONSUMEN DARI FAKTOR HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN PADA PEMAKAI SEPEDA MOTOR HONDA DAN MOTOR YAMAHA (Studi Kasus Pada Sivitas Akademika STIE AMA Salatiga) - Afandi, Pandi (AMONG MAKARTI, 2015)
AbstractConsumer in taking choice its consumption nowadays smart progressively, because given on to assorted of product choice which on the market its either from the product benefit side, its variation  its price, product  up to quality of good service of pre sell and also after sell the the product in marketing. Attitude of coir Consumer very influencing of consumer consideration in buying a[n product composed by the price factor, quality of product and quality of service which in this case concentrated to consumer / user of Honda and consumer of  Yamaha specially to sivitas of academic person in STIE AMA Salatiga.Result of research indicate that the aspect of price no difference which siginifikan  shown by value Asymp. Sig. ( 2-tailed) equal to 0,070 bigger than sig. 0,05. Consumer attitude from aspect  quality of product  no difference which signifikan shown the Asymp. Sig. ( 2-tailed) equal to 0,127 bigger than sig. 0,05. Consumer attitude from aspect of quality of service no  difference which signifikan shown by value Asymp. Sig. ( 2-tailed) equal to 0,236 bigger than sig. 0,05. attitude of Consumer of Honda and Yamaha as a whole assess the Asymp. Sig. ( 2-tailed) equal to 0,036 smaller than sig. 0,05 so that there is difference which signifikan of consumer attitude from price aspect, quality of product and quality of service at consumer of Honda and consumer of  Yamaha in  STIE AMA Salatiga.Price aspect, quality of product and quality of service and construction at sole agent of owner ( ATPM) And dealer become the very important aspect to be paid attention by each producer Honda and also producer of Yamaha. Keyword : Consumer Attitude, Price, Quality Of Product , Quality of Service.